MEMPERKAYA INTAKE PADA ADULT SECOND LANGUAGE ACQUISITION DENGAN MENGGUNAKAN NATURAL METHOD - Lusiana Indra Sari (Tarling : Journal of Language Education, 2024)
This research aims to determine effective learning methods to enrich the intake of adult second language acquisition. Teaching English as a second language has developed rapidly and produced a variety of approaches and theories. Therefore, various approaches are designed to improve second language acquisition so that it is easy to learn and well understood. The results of this research found that Natural Method is a second language teaching method that emphasizes spoken communication and direct experience in getting the meaning of a word or sentence. This method really supports learning aimed at gaining intake, especially in adult second language acquisition.